Relations between different types of children's aggressive behavior and sociometric status among peers of same and opposite gender - Keresteš, Gordana; Milanović, Anita (2006)
Croatian elementary school children in grades 4 to 6 (N = 151) reported on direct and indirect aggressive behaviors of their classmates. Acceptance and rejection by classmates were also assessed, employing the sociometric nomination technique. Correlational analyses revealed that both forms of aggression were related to peer rejection, but unrelated to peer acceptance. Girls' aggression was more strongly related to peer rejection than boys' aggression, independent of the type of aggression. Aggressive children of both gender tended to be more rejected by their same-gender classmates than by classmates of the opposite gender. Results were discussed in terms of children's attitudes towards aggression, and gender stereotyped perception of appropriateness of aggressive behavior. A need to examine developmental changes and cultural differences in relationships between aggression and peer status was emphasized.
Projekt MZOS
ENG